Physiotherapy and Nutrition: Two Unavoidable Therapies in the Treatment of Chronic non-communicable Diseases - Ismaray Sacerio González; Lourdes Elena Duany Badell; Lenia Marín Medina (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Epidemiological evidence shows that life habits, particularly dietary ones, have a direct influence on quality and life expectancy. Nutrition is one of the key factors to develop any physical activity or simply to feel well-being. The nutritional evaluation in a patient has a direct effect on the physiotherapy treatment, therefore, in order to really optimize the repair and the recovery process, the physiotherapist provides the required nutritional guidance. Only an additional intake of natural nutrients is not enough, it is necessary to complement it with other therapeutic tools within physiotherapy. People suffering from chronic diseases have transformations in eating practices, created by the underlying disease, so it is important to vary dietary habits in order to regain health. The role of the physiotherapist is decisive, to promote adherence to nutritional treatment of patients with non-communicable diseases.